2012
DOI: 10.1111/j.1741-5446.2012.00455.x
|View full text |Cite
|
Sign up to set email alerts
|

Interculturalism, Multiculturalism, and the State Funding and Regulation of Conservative Religious Schools

Abstract: In this essay, Bruce Maxwell, David Waddington, Kevin McDonough, Andrée‐Anne Cormier, and Marina Schwimmer compare two competing approaches to social integration policy, Multiculturalism and Interculturalism, from the perspective of the issue of the state funding and regulation of conservative religious schools. After identifying the key differences between Interculturalism and Multiculturalism, as well as their many similarities, the authors present an explanatory analysis of this intractable policy challenge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…These issues are matters of debate in Europe too, but no European country has come close to the view that there is no such thing as a national historic culture, and few MCs are demanding that they do, a position that comes closer to cosmopolitanism than multiculturalism. As a matter of fact, the same tensions exist within IC-Q, too (Maxwell et al, 2012). 3.…”
Section: National Culture As 'Useful and Necessary'mentioning
confidence: 74%
“…These issues are matters of debate in Europe too, but no European country has come close to the view that there is no such thing as a national historic culture, and few MCs are demanding that they do, a position that comes closer to cosmopolitanism than multiculturalism. As a matter of fact, the same tensions exist within IC-Q, too (Maxwell et al, 2012). 3.…”
Section: National Culture As 'Useful and Necessary'mentioning
confidence: 74%
“…Even though recent research has shown high levels of pro-social attitudes and behaviors among private Christian school graduates in both countries (Godwin et al 2001;Jeynes 2012;Pennings et al 2011), some researchers argue that the insularity of private Christian schools results in distrust for secular institutions and decreased political tolerance, acceptance of diversity, and civil engagement (Eamonn 1997;Kymlicka 2003;Maxwell et al 2012;Peshkin 1986;Rose 1988). Concerns about the nature and effects of religious education have led some democratic theorists to argue that while some religious schools deserve public funding, others that are "extremely" religious should be prohibited (MacMullen 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Second, one of the major concerns related to civic education is whether and how schools, especially religious schools, influence their graduates' contributions to civic and political life. While some previous studies have shown positive academic outcomes and pro-social behaviors of evangelical school graduates (Godwin, Ausbrooks, and Martinez 2001;Jeynes 2012;Pennings et al 2011), other studies argue that they contribute to decreased political tolerance, acceptance of diversity, and civil engagement (Callan 1997;Kymlicka 2003;Maxwell et al 2012;Peshkin 1986;Rose 1988). Our study examines such social attitudes.…”
mentioning
confidence: 97%
“…The issue of whether and if, how, multiculturalism and interculturalism are different has generated animated scholarly debates in the English-speaking world (Castles 2004, Bouchard 2011, Naseem 2011, Kymlicka 2012, Levey 2012, Maxwell et al 2012, Meer and Modood 2012, Taylor 2012. However, interculturalidad, multiculturalism, and interculturalism rarely appear together in the scholarly literature.…”
Section: Untangling the Differencesmentioning
confidence: 95%